Effectiveness of Pain Neuroscience Education in Physical Therapy: A Systematic Review and Meta-Analysis - Andrea Sánchez-Robalino; Hugo Sinchi-Sinchi; Andrés Ramírez (Brain Sciences)
Background: Pain neuroscience education (PNE), when combined with physical therapy interventions, has been recognized as an effective strategy for improving pain management and reducing disability in individuals with chronic pain. Objective: This systematic review and meta-analysis aimed to evaluate the effectiveness of PNE in combination with rehabilitation modalities, with a focus on pain reduction and functional improvement. Methods: A comprehensive systematic search was conducted in Cochrane, PsycInfo, PubMed, ScienceDirect, Scopus, and Web of Science databases to identify randomized clinical trials examining the effects of combining PNE with physical therapy. Nineteen studies met the inclusion criteria. Data extraction focused on demographic and methodological characteristics, as well as outcomes related to pain and disability. Results: The findings indicate that PNE combined with physical therapy significantly reduces pain intensity and enhances functionality. The mean pain score decreased from 5.89 (pre-intervention) to 3.03 (post-intervention), with similar improvements observed in disability outcomes. However, heterogeneity among studies—attributable to sociocultural and methodological differences—suggests the need for a cautious interpretation of the results. Conclusions: The integration of PNE with physical therapy appears to be an effective approach for reducing pain and improving functional outcomes in patients with chronic pain. Nevertheless, further research is recommended to address existing heterogeneity and to refine standardized intervention protocols.